Cereal foods fortified with by-products from the olive oil industry. (February 2020) - Cedola, Annamaria; Cardinali, Angela; D'Antuono, Isabella; Conte, Amalia; Del Nobile, Matteo Alessandro
Abstract: The oil industry produces large volume of waste, olive mill waste water (OMWW) and olive paste (OP), which represents a disposal and a potential environmental pollution problem. They are also promising sources of valuable compounds that can be recovered and used. The effects of OMWW and OP addition to bread and pasta, separately and combined, were studied. Both sensory and chemical properties as related to phenols content and antioxidant activity of raw materials, and fortified bread and pasta were evaluated. Results suggested that the enrichment of bread and pasta with OMWW slightly improved the chemical quality without compromising the sensory properties. While, foods enrichment with OP had considerably improved chemical quality, the sensory acceptability was worse due to the bitter and spicy taste of OP. To choose the best cereal food between bread and pasta to be enriched, a mathematical model, the whole quality index (WQI), was used. Bread was better than pasta for re-using olive oil by-products. Between OMWW and OP, the latter was more suitable for food fortification, despite the sensory problems of the enriched product. Also, when the two by-products were combined, the best product continued to be the bread.